Anxiety, Depression And Adaptacion Psychosocial in Adult Patients with Type 2 DM - Osorio Aquino, Marina del carmen (Horizonte Sanitario, 2021)
Summary: In 2017 there was a figure of 245 million people with Diabetes (DM) in the world. It is expected that by the 2045 there will be an increase of 48% which would give us 629 million patients. Objective: To determine the relationship of anxiety, depression and psychosocial adaptation of patients with T2DM. Material and Methods: The selected design was descriptive and correlational. The Population consisted of 103 adults between 20 and 60 years of age with a diagnosis of T2DM who attended the CESSA. Maximiliano Dorantes. With Probability Sampling. Results: It is observed that 32% have moderate anxiety and only 68% present low anxiety, as for depression 90.3% and 9.7% do not have depression. A significant negative was found between anxiety and health care (-3.57 **, p = .000), which indicates that the more anxiety there is, the maladaptation. A positive negative (-.642 **, p = .000) was obtained between anxiety and work environment, that is, the greater the anxiety, the poor adaptation. A significant denial was found between depression and work environment (.530 **, p = .000), which indicates greater depression, maladaptation. Conclusion: When patients lose the ability to cope, they fall into depression and anxiety can be mild, moderate or high. This largely depends on the support they receive from their family members. The psychosocial adaptation that each individual experiences varies according to the environment in which they find themselves, some have the support of their relatives but do not have the economic resource, others have the economic ease but do not have the support of their relatives They have to adapt to the new changes in their daily life, which is not and will not be easy, if they do not have any kind of help. Keywords: Anxiety, Depression, Adaptation Psychologic and elderly